Cooperative Work a Fundamental Strategy in Primary Education - SOLIS, Amparo Rosa Montellanos; PIMENTEL, Johnny Félix Farfán; RIVEROS, Janet Meluzka García; MEZA, Luis Carmelo Fuertes (PT Keberlanjutan Strategis Indonesia, 2021)
This article provides an analysis, review of the different bibliographic sources about cooperative work as a fundamental strategy for the acquisition of competences, which strengthens interpersonal relationships, construction of new knowledge, attitudes and the management of skills such as communication, autonomy, leadership, decision-making, motivation in primary school students since at this level, learning depends not only on a single student but on the effort of the group as a whole to achieve the expected purpose. At present it is a relevant issue since it is a strategy that seeks methodological, active, participatory, dynamic change, awakens the interest of students to discover, learn, innovate, internalize, consolidate learning cooperatively working in small groups to expand their learning, seeking the benefit of all in which they assume the role of protagonists of their own learning developing in different contexts, work in a climate of satisfaction, understanding, respect and tolerance. In the first instance, the different conceptions about cooperative work by recognized authors are made known. Second, information is provided on the characteristics, importance of cooperative work, the structure used by the teacher to carry out the activities. Finally, significant contributions of cooperative.